Strategi Promosi dan Pengelolaan Peserta Didik Baru di Sekolah Dasar melalui Media Sosial - Berliana Rizka Nadua; Choerunisa Fatin Mujah; Auliya, Marisa Dewi; Zulfie, Syafril Ammar; Putra, Lisa Virdinarti (Yayasan Literasi Sains Indonesia, 2025)
Student admission at the elementary school level is more than just an administrative process it serves as a crucial entry point for effective student management. This study aims to explore the strategies used in managing students during the new student admission process and to identify the challenges faced by schools, along with how they address these issues. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis at several public and private elementary schools. The findings reveal that the student admission process goes beyond registration; it includes planning the number of new students, conducting transparent selection procedures, and organizing orientation programs to help students adapt. Key challenges include the zoning system, limited facilities, and a lack of information provided to parents. However, schools that promote open communication, utilize technology, and routinely evaluate their admission practices show better readiness in creating a supportive learning environment. The study recommends strengthening school management capacity to ensure a fair, efficient, and sustainable student admission and management system.